On $θ$-$b$-Irresolute Functions - Rajesh, N. (Sarajevo Journal of Mathematics, 2024)
The concept of $b$-open sets was introduced by Andrijevic. The aim of this paper is to introduce and characterize $θ$-$b$-irresolute functions by using $b$-open sets. 2000 Mathematics Subject Classification. 54C05